Sport injuries in elite paralympic swimmers with visual impairment - Magno e Silva, M.; Bilzon, J.; Duarte, E.; Gorla, J.; Vital, R. (Journal of Athletic Training, 2013)
Context: Visually impaired athletes sustain overuse injuries in the lower limbs, but the pattern of injuries may vary according to the sport. The characteristics of sports injuries in visually impaired swimmers are unknown. Objective: To determine the characteristics and epidemiologic measures (prevalence, clinical incidence, and incidence rate) of sports injuries in visually impaired elite national swimmers and to assess differences among visual classes and between sexes. Design: Descriptive epidemiology study. Setting: International Paralympic competitions held between 2004 and 2008. Patients or Other Participants: Twenty-eight elite, visually impaired swimmers (19 males, 9 females) from the Brazilian Paralympic Team participated in this study. Twelve were visual class S11 (blind swimmers), 12 were S12 (low-vision swimmers), and 4 were S13 (low-vision swimmers). Intervention(s): A standardized report form was used to collect data during 5 competitions. This was endorsed by 2 Brazilian sports governing bodies. Main Outcome Measures: The characteristics, prevalence, clinical incidence, and incidence rate of injuries were calculated. Results: Eighteen athletes reported 41 sports injuries, with a prevalence of 64%, clinical incidence of 1.5 injuries per athlete, and an incidence rate of 0.3 injuries per athlete per competition. Overuse injuries (80%) were more frequent than traumatic injuries (20%). The clinical incidence and prevalence varied according to sex and visual class, but no statistical differences were observed (P > .05). The highest proportion of injuries was in the trunk (46.34%), followed by the upper limbs (34.15%). The shoulders (29.27%) were most affected, followed by the thoracic (21.95%) and lumbar spine (17.07%). Spasm (36.59%) was the most frequent diagnosis, followed by tendinopathy (26.83%). Conclusions: Visually impaired swimmers had a relatively high proportion of overuse injuries, predominantly associated with muscle spasm in the spine and tendinopathy in the shoulders. No differences were apparent in injury prevalence and clinical incidence among visual classes or between sexes.